2020
DOI: 10.1097/md.0000000000020056
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle metastasis as a first site of recurrence of cervical cancer

Abstract: Rationale: Cervical cancer primarily spreads through direct invasion or via local lymphatics, and hematogenous metastasis is infrequent. Previous reports have shown that lung, liver, and bone are the organs most frequently affected by hematogenous metastasis of cervical cancer, while skeletal muscle is very rarely involved. Patient concerns: A 75-year-old Japanese woman presented with a painful muscular mass in her right lower abdomen. Five years ago, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Kim et al ( 24 ) recommended surgical resection or external radiotherapy for isolated masses without other metastases. Omokawa et al ( 25 ) reported a case of SMM from cervical cancer; they performed limited surgical procedures, and the patient was free of disease at ten months after the development of recurrent disease. However, Li et al ( 19 ) reported a case of PCCA with SMM in which the patient died two months later after a 5-day course of 20 Gy external beam radiation in five fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al ( 24 ) recommended surgical resection or external radiotherapy for isolated masses without other metastases. Omokawa et al ( 25 ) reported a case of SMM from cervical cancer; they performed limited surgical procedures, and the patient was free of disease at ten months after the development of recurrent disease. However, Li et al ( 19 ) reported a case of PCCA with SMM in which the patient died two months later after a 5-day course of 20 Gy external beam radiation in five fractions.…”
Section: Discussionmentioning
confidence: 99%